Biomarkers of Response to Internet-Based Psychological Interventions: Systematic Review - Giulia Gotti; Chiara Gabelli; Sophia Russotto; Fabio Madeddu; Philippe Courtet; Jorge Lopez-Castroman; Patrizia Zeppegno; Carla Maria Gramaglia; Raffaella Calati (JMIR Publications, 2024)
BackgroundInternet-based psychological interventions provide accessible care to a wide range of users, overcoming some obstacles-such as distance, costs, and safety-that might discourage seeking help for mental issues. It is well known that psychological treatments and programs affect the body, as well as the mind, producing physiological changes that ought to be considered when assessing the efficacy of the intervention. However, the literature investigating changes in biomarkers specifically after internet-based psychological and mental health interventions has not yet extensively inquired into this topic. ObjectiveThis systematic review aims to provide a synthesis of literature examining the effects of internet-based psychological interventions-targeting both clinical (mental and physical) and nonclinical conditions-on biomarkers. A secondary aim was to evaluate whether the biomarkers' variations were related to a complementary modification of the psychological or physical symptoms or to a general improvement of the participants' well-being. MethodsThis review was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) statement. A literature search was performed through 3 databases (PubMed, PsycINFO, and Scopus). Studies examining changes in biomarkers before and after internet-based psychological interventions or programs targeting both clinical and nonclinical samples were included, with no exclusion criteria concerning mental or physical conditions. ResultsA total of 24 studies fulfilled the inclusion criteria. These studies involved individuals with psychiatric or psychological problems (n=6, 25%), those with organic or medical diseases (n=10, 42%), and nonclinical populations (n=8, 33%). Concerning psychiatric or psychological problems, cognitive behavioral therapy (CBT) and CBT-informed interventions showed partial effectiveness in decreasing glycated hemoglobin blood glucose level (n=1) and chemokines (n=1) and in increasing connectivity between the default-mode network and the premotor or dorsolateral prefrontal cortex (n=1). Among individuals with organic or medical diseases, studies reported a significant change in cardiac or cardiovascular (n=3), inflammatory (n=2), cortisol (n=2), glycated hemoglobin (n=2), and immune response (n=1) biomarkers after CBT and CBT-informed interventions, and mindfulness and stress management interventions. Lastly, mindfulness, CBT and CBT-informed interventions, and music therapy succeeded in modifying immune response (n=2), cortisol (n=1), α amylase (n=1), posterior cingulate cortex reactivity to smoking cues (n=1), and carbon monoxide (n=1) levels in nonclinical populations. In some of the included studies (n=5), the psychological intervention or program also produced an improvement of the mental or physical condition of the participants or of their general well-being, alongside significant variations in biomarkers; CBT and CBT-informed interventions proved effective in reducing both psychological (n=2) and physical symptoms (n=2), while a mindfulness program successfully lowered cigarette consumption in a nonclinical sample (n=1). ConclusionsAlthough further evidence is required, we hope to raise awareness on the potential impact of internet-based interventions on biomarkers related to mental and physical health.